Marketing Communications Management in the Public Administration System - Shevchenko, Inna Yu.; Nepomnyashchyy, Oleksandr M.; Marusheva, Oleksandra A.; Medvedchuk, Oksana V.; Lahunova, Iryna A. (International Journal of Criminology and Sociology, 2021)
The issues of building effective marketing communications systems at the level of public administration are discussed in the article. Most marketing communications research focuses on the private sector. Marketing communications in the public sector are comprehensive and multi-functional. So, marketing communications in public administration are considered not only as a complex of information and communication mechanisms. They also include political, social, economic and cultural aspects. The marketing communications system should be formed both on the domestic market (provision of administrative services to the population and formation of a positive image of state power) and external (establishment of cooperation with international partners and conduct of international policy). According to statistics, the system of information support of public administration is considered relevant by more than 60% of the population of Ukraine. Therefore, given the relevance of this issue, it is useful to determine its practical significance. The establishment of a marketing communications system in public administration should provide the population with mobile provision of administrative services of high quality, the creation of systems of democratic civil society through the development of electronic petitions, the formation of a favorable image of the state to ensure high support for the processes of state creation among the population and at the international level to attract additional investments and ensure tourist attractiveness. Among the current directions of development of marketing communications of public administration are advertising, PR-technologies, image and brand construction, fight against “negative” and fake information, provision of electronic management and provision of administrative services online. However, providing the population with access to the Internet also remains an important issue, as it is this resource that is the main one for the introduction of digitization and digitalization processes in the country.